2018
DOI: 10.3389/fcimb.2018.00427
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis IgG1 Rapid Monitoring of Cure vs. Relapse, and Potential for Diagnosis of Post Kala-Azar Dermal Leishmaniasis

Abstract: Background: There is a recognized need for an improved diagnostic test to assess post-chemotherapeutic treatment outcome in visceral leishmaniasis (VL) and to diagnose post kala-azar dermal leishmaniasis (PKDL). We previously demonstrated by ELISA and a prototype novel rapid diagnostic test (RDT), that high anti-Leishmania IgG1 is associated with post-treatment relapse versus cure in VL.Methodology: Here, we further evaluate this novel, low-cost RDT, named VL Sero K-SeT, and ELISA for monitoring IgG1 levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The only antigen detecting test evaluated here did not prove valuable because of its very low specificity. Previously, IgG1 was found to be the predominant antibody present in VL infection and has been explored as a potential biomarker of post-chemotherapeutic relapse [ 34 , 35 ]. Therefore it was hypothesized that IgG1 detection may also be useful in predicting progression to VL infection among asymptomatic patients which was previously supported by some limited data [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only antigen detecting test evaluated here did not prove valuable because of its very low specificity. Previously, IgG1 was found to be the predominant antibody present in VL infection and has been explored as a potential biomarker of post-chemotherapeutic relapse [ 34 , 35 ]. Therefore it was hypothesized that IgG1 detection may also be useful in predicting progression to VL infection among asymptomatic patients which was previously supported by some limited data [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gold-standard diagnosis by detection of the parasite in tissue specimens is not possible in most rural health facilities. Rapid serological tests provide an alternative, but the rK39 antigen-based test has proven less sensitive in Sudan than in the Indian subcontinent32 and the test has a relatively short shelf-life which can make it uneconomical to keep supplies outside of major centres 33. Ongoing work has been seeking to address the need for cheap, sensitive, specific and sustainable rapid diagnostics for Sudanese visceral leishmaniasis, which will help to better define disease burden, identify cases for prompt treatment and potentially allow confirmation of post-treatment cure 32–34…”
Section: Communicable Diseasesmentioning
confidence: 99%
“…Evaluation in PKDL showed that the VL sero K-set and IgG1 ELISA supported PKDL diagnosis with a strong correlation with post VL samples, suggesting persistence of antibodies after VL. No association was found between elevated IgG1 and macular or polymorphic PKDL lesions (Marlais et al, 2018). IgG1 levels did not show a consistent decrease 1 year after PKDL treatment (Marlais et al, 2018).…”
Section: Laboratory Biomarkersmentioning
confidence: 99%
“…No association was found between elevated IgG1 and macular or polymorphic PKDL lesions (Marlais et al, 2018). IgG1 levels did not show a consistent decrease 1 year after PKDL treatment (Marlais et al, 2018).…”
Section: Laboratory Biomarkersmentioning
confidence: 99%